The dynamics of managing the Nigerian financial system in the 21st century - Nnanna, O. J.; Central Bank of Nigeria (Abuja Central Bank of Nigeria, 1998)
This book is a proceeding of a two day seminar on the dynamics of managing the Nigerian financial system in the 21 century and the challenges for the next millennium held at the Hill Station Hotel, Jos between September 17-19, 1998
lje 22/08/16
Loan
Keywords: Finance; Financial institutions, Management